Vertex Green's Functions of a Quarter-Plane: Links Between the Functional Equation, Additive Crossing and Lamé Functions. Issue 3 (15th May 2021) - Assier, R C; Shanin, A V
Summary: In our previous work (R. C. Assier and A. V. Shanin, Q. J. Mech. Appl. Math., 72, 2019), we gave a new spectral formulation in two complex variables associated with the problem of plane-wave diffraction by a quarter-plane. In particular, we showed that the unknown spectral function satisfies a condition of additive crossing about its branch set. In this article, we study a very similar class of spectral problem and show how the additive crossing can be exploited in order to express its solution in terms of Lamé functions. The solutions obtained can be thought of as tailored vertex Green's functions whose behaviours in the near-field are directly related to the eigenvalues of the Laplace–Beltrami operator. This is important since the correct near-field behaviour at the tip of the quarter-plane had so far never been obtained via a multivariable complex analysis approach.